AUDIT DATA AKUNTANSI TERKOMPUTERISASI - Aris Eddy Sarwono (Universitas Slamet Riyadi, 2009)
Abstract Financial statement represent the form of management responsibility to party side of outside company to the financial position and result of company operation of during an specified period (usually one year). Financial statement compiled by pursuant to standard of accountancy and inveterate practice accountancy in the world of accountancy. Accountancy standard published by accountant profession by the name of financial accounting standard. This accountancy Standard is made by reference by all side which is related to financial statement. In course of compilation of financial statement conducted by manual or computerized. When used by the way of manual of hence will be used by documents and accountancy note of like journal, general ledger, trial balance etcetera. When used by computer of hence some note of accountancy and document will becoming not there is because direct processed in computer or saving on form the file. Keywords: audit, financial statement, financial statement standard